Magnetic composite photocatalyst for removing tetracycline as well as preparation method and application of magnetic composite photocatalyst
By developing a magnetic composite photocatalyst containing oxyferric chloride, zinc ferrite and ferric oxide, the problems of low efficiency and high cost of existing photocatalysts in removing tetracycline have been solved, and efficient and environmentally friendly tetracycline removal has been achieved effect, and reduces production costs through magnetic recycling.
Patent Information
- Application Number
- CN202411458428.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The existing photocatalysts are inefficient when removing tetracycline in water, and need to form a photofenton system with H2O2 to achieve a higher degradation rate, resulting in increased costs and reduced catalyst activity.
Develop a magnetic composite photocatalyst, containing oxyferric chloride, zinc ferrite and ferric oxide, prepared through the complexation reaction of choline chloride, glycerol, water, zinc source, iron source and citric acid , is magnetic and recyclable, and does not need to form a photo-Fenton system with H2O2 to efficiently remove tetracycline.
The efficient removal of tetracycline is achieved with high removal rate and short removal time, and the magnetic composite photocatalyst can be recovered by applying an external magnetic field, reducing production costs and environmental risks.
Smart Images

Figure CN119303602A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalytic materials and wastewater treatment, and in particular to a magnetic composite photocatalyst for removing tetracycline, and a preparation method and application thereof. Background Art
[0002] Antibiotic wastewater mainly comes from hospitals, pharmaceutical industry, animal husbandry, aquaculture industry and other fields. Antibiotics are new pollutant wastewaters with biological toxicity, environmental persistence and accumulation, and pose a potential threat to human health and the ecological environment. According to existing data, only about 10-20% of antibiotics are metabolized by organisms, and the unmetabolized part is directly or indirectly discharged into the water environment. Therefore, how to effectively remove residual antibiotics has become a research hotspot in recent years, making the removal of trace antibiotics in water bodies a problem to be solved.
[0003] Tetracycline antibiotics are widely used as broad-spectrum antibiotics. Tetracycline antibiotics have a common chemical structure matrix, mainly including tetracycline, chlortetracycline, oxytetracycline, doxycycline, etc. The removal methods of tetracycline antibiotics mainly include advanced oxidation method, adsorption method, microbial treatment method, etc. Traditional urban sewage treatment methods mainly focus on removing suspended solids, organic matter, nitrogen, phosphorus and other components in sewage, while the removal of trace drugs and antibiotics is relatively limited.
[0004] Existing methods for removing tetracycline antibiotics in water environments include photocatalytic oxidation technology. Photocatalytic oxidation technology mainly refers to the transition of electrons in the valence band of the semiconductor to the conduction band after the photocatalyst is irradiated by the light source, forming photogenerated electrons (e - )-hole (h + Yes, + It has oxidizing properties and can convert OH - and H 2 O is oxidized to hydroxyl radical (·OH); e - It has reducing properties and can react with O 2 The reaction generates superoxide free radicals (·O 2 - );h + , ·OH, ·O 2 - Various active free radicals such as TiO can mineralize organic matter such as antibiotics in water. 2 and their composites as photocatalytic materials, however, TiO 2 The property of responding only to ultraviolet light limits its utilization of visible light, which accounts for 48% of the energy of the solar spectrum.
[0005] Ferric chloride (FeOCl) is an n-type semiconductor photocatalyst with a stable structure. Its narrow bandgap of 1.6eV-1.8eV makes it have good visible light response ability. However, its relatively high e - and h + The probability of recombination is low, which results in that although it has photocatalytic ability, its photocatalytic activity is not significant. Therefore, FeOCl usually needs to be combined with H 2 O 2 Combined to form a photo-Fenton system. As a photo-Fenton catalyst, FeOCl can be used for the photocatalytic degradation of tetracycline hydrochloride. However, FeOCl has obvious shortcomings when used alone as a photocatalyst or a photo-Fenton catalyst. The main manifestations are: the core of FeOCl's good catalytic performance is that its surface has a very rich Fe 2+ and Fe 3+ Active sites, under light conditions, when the irradiation energy is greater than the band gap energy of the semiconductor material, the internal electrons will change from the ground state to the excited state, cross the forbidden band, reach the higher energy level of the conduction band, and leave a large number of holes in the valence band. 3+ It can also capture photogenerated electrons to form Fe 2+ , and then Fe 2+ Will continue with O 2- The reaction generates ·OH, ·O 2- and Fe 3+ However, as the number of transformations increases, some iron ions will be lost, resulting in a decrease in the conversion rate of electron-hole pairs; during the photo-Fenton catalytic process, the iron atoms in FeOCl are also easy to flow out and dissolve in the solution, resulting in a decrease or loss of the overall catalyst activity; the outflow of iron atoms can easily cause catalyst agglomeration, which is not conducive to long-term photo-Fenton catalytic reaction, and the catalyst needs to be continuously supplemented or replaced, which increases the cost of photo-Fenton catalytic degradation of pollutants to a certain extent; the low separation efficiency of photogenerated electron-hole pairs also limits the catalytic activity of FeOCl as a photo-Fenton catalyst.
[0006] In the prior art, FeOCl@COF-JLU19 composite material is obtained by compounding FeOCl with COFs material. The photocatalytic activity of the composite material to tetracycline hydrochloride is significantly improved. However, it still requires H 2 O 2 The formed photo-Fenton system can achieve a higher degradation rate.
[0007] The prior art also uses TiO 2 and MoS 2 Combined with FeOCl to form TiO 2 @FeOCl composite photocatalyst and MoS 2 @FeOCl composite photocatalyst, without H2 O 2 Under these conditions, TiO 2 @FeOCl and MoS 2 The degradation rate of Rhodamine B at a concentration of 4 mg / L by the @FeOCl composite photocatalyst was nearly doubled and doubled compared with FeOCl, and the degradation rates of Rhodamine B were about 63% and 98% at 120 min, respectively. However, the multi-component composition of such composite catalysts usually requires multi-step synthesis, which is cumbersome and relatively costly; at the same time, the smaller particle size makes it relatively difficult to recycle.
[0008] Therefore, it is of great significance to utilize the existing advantages of FeOCl to develop new and efficient magnetic FeOCl composite visible light catalysts, improve the utilization rate of light energy, reduce the recombination probability of FeOCl photogenerated electron-hole pairs, and utilize its magnetism to achieve its recovery through an external magnetic field.
[0009] In view of this, the present invention is proposed. Summary of the invention
[0010] The first object of the present invention is to provide a method for preparing a magnetic composite photocatalyst for removing tetracycline. The method can be used to prepare a magnetic composite photocatalyst containing oxyferric chloride, zinc ferrite and ferric oxide. The magnetic composite photocatalyst can effectively remove tetracycline in water, has a high removal rate and a short removal time. The preparation method is simple, the recovery difficulty of the magnetic composite photocatalyst is low, and the magnetic composite photocatalyst does not need to be reacted with H 2 O 2 A very high degradation rate can be achieved by forming a photo-Fenton system.
[0011] The second object of the present invention is to provide a magnetic composite photocatalyst for removing tetracycline, which has a good degradation effect on tetracycline, a high removal rate, a short removal time, and a low recovery difficulty, and the magnetic composite photocatalyst does not need to be combined with H 2 O 2 A higher degradation rate can be achieved by forming a photo-Fenton system.
[0012] The third object of the present invention is to provide an application of a magnetic composite photocatalyst for removing tetracycline.
[0013] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0014] The present invention first provides a method for preparing a magnetic composite photocatalyst for removing tetracycline, comprising the following steps:
[0015] The choline chloride, glycerol, water, zinc source, iron source and citric acid are mixed and subjected to complex reaction to obtain a sol; the pH of the sol is adjusted and then heated to obtain a gel; the gel is ignited to obtain a precursor; the precursor is calcined to obtain the magnetic composite photocatalyst for removing tetracycline;
[0016] Wherein, the molar ratio of the zinc element in the zinc source to the iron element in the iron source is 1:1.4-2.4.
[0018] The molar ratio of the choline chloride to the glycerol is 0.5-1.5:1.5-2.5.
[0019] The ratio of the sum of the volumes of the choline chloride and the glycerol to the volume of the water is 10-25:2-20.
[0020] Furthermore, the ratio of the molar amount of the citric acid to the sum of the molar amounts of the zinc element in the zinc source and the iron element in the iron source is 0.75-1.25:1.
[0021] Furthermore, the ratio of the sum of the volumes of the choline chloride, the glycerol and the water to the molar amount of the zinc element in the zinc source is 20-100 mL:1 mol.
[0022] Furthermore, the temperature of the complexation reaction is 40-95°C.
[0023] Furthermore, the pH of the sol is adjusted to a pH range of 7.5-9.
[0024] Furthermore, the calcination temperature is 500-1000°C.
[0025] Furthermore, the calcination holding time is ≥40 min.
[0026] Furthermore, the calcination further includes the steps of washing and drying.
[0027] The present invention further provides a magnetic composite photocatalyst for removing tetracycline, which is mainly prepared by the preparation method of the magnetic composite photocatalyst for removing tetracycline. The magnetic composite photocatalyst for removing tetracycline comprises oxyferric chloride, zinc ferrite and ferric oxide.
[0028] The invention also provides application of the magnetic composite photocatalyst for removing tetracycline in removing tetracycline.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The magnetic composite photocatalyst prepared by the method for preparing a tetracycline removal magnetic composite photocatalyst provided by the present invention contains oxyferric chloride, zinc ferrite and ferric oxide. The magnetic composite photocatalyst has a good degradation effect on tetracycline, a high removal rate, and a short removal time. The preparation method is simple, the recovery difficulty of the magnetic composite photocatalyst is low, and the magnetic composite photocatalyst does not need to be mixed with H 2 O 2 A very high degradation rate can be achieved by forming a photo-Fenton system.
[0031] (2) The magnetic composite photocatalyst prepared by the method for preparing the tetracycline-removing magnetic composite photocatalyst provided by the present invention has magnetism, can be recovered and reused multiple times by applying an external magnetic field, is easy to recycle, and is environmentally friendly and energy-saving.
[0032] (3) The preparation method of the magnetic composite photocatalyst for removing tetracycline provided by the present invention is easy to operate, has a short process flow, is suitable for large-scale production, has low raw material cost, and has high product added value. The magnetic composite photocatalyst prepared by the method can be widely used in tetracycline wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 The XRD diagram of the magnetic composite photocatalyst prepared in Example 1 provided by the present invention;
[0035] Figure 2 A curve diagram showing the change in the removal rate of the tetracycline solution by the magnetic composite photocatalyst prepared in Example 1 provided by the present invention as a function of the treatment time;
[0036] Figure 3 A curve diagram showing the change in the removal rate of the tetracycline solution by the magnetic composite photocatalyst prepared in Example 2 provided by the present invention as a function of the treatment time;
[0037] Figure 4 A curve diagram showing the change in the removal rate of the tetracycline solution by the magnetic composite photocatalyst prepared in Example 3 provided by the present invention as a function of the treatment time;
[0038] Figure 5 A curve diagram showing the change in the removal rate of the tetracycline solution by the magnetic composite photocatalyst prepared in Example 4 provided by the present invention as a function of the treatment time;
[0039] Figure 6 This is a comparison chart of the removal rate of tetracycline in the first photocatalytic tetracycline solution experiment and three repeated recyclings of the magnetic composite photocatalyst prepared in Example 3 provided by the present invention. DETAILED DESCRIPTION
[0040] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0041] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0042] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0043] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0044] In a first aspect, the present invention provides a method for preparing a magnetic composite photocatalyst for removing tetracycline, comprising the following steps:
[0045] Choline chloride, glycerol, water, a zinc source, an iron source and citric acid are mixed and subjected to a complex reaction to obtain a sol; the pH of the sol is adjusted and then heated to obtain a gel; the gel is ignited to obtain a precursor; the precursor is calcined, cooled, washed with water and dried to obtain the magnetic composite photocatalyst for removing tetracycline.
[0046] Wherein, the molar ratio of the zinc element in the zinc source to the iron element in the iron source is 1:
[0047] 1.4-2.4; including but not limited to any point value of 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4 or the range value between any two of them.
[0048] The molar ratio of the choline chloride to the glycerol is 0.5-1.5:1.5-2.5, including but not limited to any one of 0.5:1.5, 1:1.5, 1.5:1.5, 0.5:2, 1:2, 1.5:2, 0.5:2.5, 1:2.5, 1.5:2.5 or any range between two thereof.
[0049] The ratio of the sum of the volumes of the choline chloride and the glycerol to the volume of the water is 10-25:2-20, including but not limited to any one of 10:20, 15:15, 20:10, 25:5 or a range between any two of them.
[0050] The magnetic composite photocatalyst for removing tetracycline provided by the present invention adds a low eutectic solvent during the preparation process, and the low eutectic solvent can change the ionic strength, solubility, etc. of the reaction system; the low eutectic solvent also participates in the reaction, and the choline chloride in the low eutectic solvent can also be used as a chlorine source to react with the iron complex or oxide to generate oxyferric chloride during the calcination process, thereby changing the mechanism and pathway of the reaction; the addition of the low eutectic solvent may also affect the rate and kinetics of the reaction, and change the conditions of the oxidation reaction. These factors affect the composition of the product and cause side reactions to occur, so the magnetic composite photocatalyst contains oxyferric chloride (FeOCl), zinc ferrite and ferric oxide. The magnetic composite photocatalyst has a good degradation effect on tetracycline, a high removal rate, a short removal time, and the magnetic composite photocatalyst does not need to be oxidized with H 2 O 2 A very high degradation rate can be achieved by forming a photo-Fenton system.
[0051] In addition, the magnetic composite photocatalyst is magnetic and can be recovered and reused multiple times through an external magnetic field. The recovery is easy and it is environmentally friendly and energy-saving.
[0052] Specifically, the present invention uses a mixed solution of choline chloride, glycerol and water as a solvent. The electrostatic effect of the anions and cations in the mixture can make the metal complex formed by the iron salt and the divalent metal salt and the complexing agent more stably and evenly dispersed in the sol-gel during the formation of the sol and gel, which is conducive to the nanoparticles in the precursor being small and uniform, and the metal ions being more evenly dispersed therein, so that the spatial arrangement of the gel during the formation process is more regular, thereby increasing the specific surface area of the product, the dispersion uniformity of the components in the product, and the interaction between the components in the product, thereby improving the photocatalytic performance and magnetic recoverability of the magnetic composite photocatalyst.
[0053] Among them, by adjusting the pH of the sol, the formation and stability of the sol, the morphology and structure of the gel, and the stability of the metal ions can be controlled, thereby controlling the microstructure and properties of the material.
[0054] Before the precursor is formed, it is ignited in a gel state to allow the nitrate in it to fully react, thereby accelerating the reaction rate, shortening the reaction time, and optimizing the preparation process. Compared with heating the gel, the gel can be ignited at room temperature, which is simple to operate and consumes less energy. During the preparation of the magnetic composite catalyst, metal ions are added to increase the ferromagnetism of the photocatalyst, thereby facilitating the separation and recycling of the photocatalyst.
[0055] In addition, the preparation method of the magnetic composite photocatalyst for removing tetracycline provided by the present invention is simple to operate, has a short process, is suitable for large-scale production, has low raw material cost, and has high product added value. The magnetic composite photocatalyst prepared by the method can be widely used in antibiotic wastewater treatment.
[0056] In some specific embodiments, the preparation method of the magnetic composite photocatalyst for removing tetracycline specifically includes: first mixing choline chloride, propylene glycol and water evenly, then adding a zinc source and an iron source thereto, stirring for a period of time, adding citric acid thereto to carry out a complex reaction, and after reacting for a period of time, adding an alkali solution such as an ammonia solution thereto to adjust the pH of the reaction system to obtain a sol; heating the sol to gradually form a gel, and igniting the gel to obtain a precursor; calcining the precursor and cooling it to obtain a magnetic composite photocatalyst.
[0057] In some specific embodiments, the zinc source includes a zinc-containing compound, such as zinc nitrate, but is not limited thereto.
[0058] In some specific embodiments, the iron source includes an iron-containing compound, such as ferric nitrate, but is not limited thereto.
[0059] In order to further improve the degradation effect of the magnetic composite photocatalyst on tetracycline, increase the removal rate, and shorten the removal time, the present invention optimizes the parameters such as the amount of citric acid, the pH value during the reaction, and the temperature and time during the preparation process as follows.
[0060] In some specific embodiments, the ratio of the molar amount of citric acid to the sum of the molar amounts of zinc in the zinc source and iron in the iron source is 0.75-1.25:1, including but not limited to any one of 0.75:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.25:1 or a range between any two of them.
[0061] In some specific embodiments, the ratio of the sum of the volumes of the choline chloride, the glycerol and the water to the molar amount of the zinc element in the zinc source is 20-100 mL (including but not limited to any one of 20 mL, 30 mL, 50 mL, 60 mL, 80 mL, 100 mL or a range between any two of them): 1 mol.
[0062] In some specific embodiments, the temperature of the complexation reaction is 40-95°C, including but not limited to any point value of 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 95°C or a range between any two of them.
[0063] In some specific embodiments, the reaction time of the complex reaction is ≥20 min, including but not limited to any one of 20 min, 30 min, 40 min, 50 min, 60 min, 120 min, 180 min, 240 min, 300 min or a range between any two of them.
[0064] In some specific embodiments, the pH of the sol is adjusted to a pH range of 7.5 to 9, including but not limited to any one of 7.5, 8, 8.5, 9 or a range between any two of them.
[0065] In some specific embodiments, the calcination temperature is 500-1000°C, including but not limited to any point value of 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C or any range value between two of them.
[0066] In some specific embodiments, the calcination holding time is ≥40 min, including but not limited to any one of 40 min, 1 h, 2 h, 3 h, 4 h, 6 h, 8 h, 10 h, 12 h, 15 h, 20 h, and 24 h, or a range between any two of them.
[0067] In some specific embodiments, the calcination further comprises the steps of water washing and drying.
[0068] In a second aspect, the present invention provides a magnetic composite photocatalyst for removing tetracycline, which is mainly prepared by the preparation method of the magnetic composite photocatalyst for removing tetracycline. The magnetic composite photocatalyst for removing tetracycline includes oxyferric chloride, zinc ferrite and ferric oxide.
[0069] The magnetic composite photocatalyst has a good degradation effect on tetracycline, with a high removal rate, a short removal time and low recovery difficulty.
[0070] In addition, the magnetic composite photocatalyst has magnetism and can be recovered and reused multiple times through an external magnetic field, which is environmentally friendly and energy-saving.
[0071] In a third aspect, the present invention provides the use of the magnetic composite photocatalyst for removing tetracycline in removing tetracycline.
[0072] The magnetic composite photocatalyst has a good degradation effect on tetracycline, with a high removal rate and a short removal time. It can also be recycled and reused with a high reuse removal rate, and can be widely used in tetracycline wastewater treatment.
[0073] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0074] Example 1
[0075] The preparation method of the magnetic composite photocatalyst for removing tetracycline provided in this embodiment comprises the following steps: choline chloride and glycerol are mixed in a molar ratio of 1:2 to prepare a choline chloride-glycerol mixed solution, and the choline chloride-glycerol mixed solution is mixed with water in a volume ratio of 18:12 to obtain a mixed solution of choline chloride-glycerol-water. 1 mol of zinc nitrate and 2 mol of ferric nitrate weighed in advance are added to the mixed solution of choline chloride-glycerol-water with a total volume of 30 mL and stirred evenly, and then 3 mol of citric acid is added thereto, and a complex reaction is carried out at 60°C to obtain a sol, and then the pH value of the sol is adjusted to 7.5 with ammonia water, and then heated continuously to form a gel, and after the gel is dried, a small amount of ethanol is added thereto and ignited, and after the combustion reaction is completed, a precursor is obtained. The precursor is calcined at 750°C for 2h, cooled and washed with water to obtain a magnetic composite photocatalyst for removing tetracycline.
[0076] like Figure 1The XRD pattern of the magnetic composite photocatalyst prepared in this example is shown in FIG. Figure 1 It can be seen that the main components of the magnetic composite photocatalyst prepared in this embodiment are oxyferric chloride, zinc ferrite and ferric oxide.
[0077] Example 2
[0078] The preparation method of the magnetic composite photocatalyst for removing tetracycline provided in this embodiment is basically the same as that in Example 1, except that choline chloride and glycerol are mixed in a molar ratio of 1:1.5 to prepare a choline chloride-glycerol mixed solution, and the choline chloride-glycerol mixed solution is mixed with water in a volume ratio of 20:10 to obtain a choline chloride-glycerol-water mixed solution.
[0079] Example 3
[0080] The preparation method of the magnetic composite photocatalyst for removing tetracycline provided in this embodiment is basically the same as that in Embodiment 1, except that the pH value of the sol is adjusted to 8.5 with ammonia water.
[0081] Example 4
[0082] The preparation method of the magnetic composite photocatalyst for removing tetracycline provided in this embodiment is basically the same as that in Example 1, except that the pH value of the sol is adjusted to 8 with ammonia water, and the temperature of the precursor calcination is replaced with 550° C. and the insulation time is replaced with 6 hours.
[0083] Example 5
[0084] The preparation method of the magnetic composite photocatalyst for removing tetracycline provided in this embodiment is basically the same as that in Example 1, except that the holding time of the precursor calcination is replaced with 4 hours.
[0085] Example 6
[0086] The preparation method of the magnetic composite photocatalyst for removing tetracycline provided in this embodiment is basically the same as that in Example 1, except that the molar amount of zinc nitrate is replaced by 1 mol, and the molar amount of iron nitrate is replaced by 2.4 mol.
[0087] Example 7
[0088] The preparation method of the magnetic composite photocatalyst for removing tetracycline provided in this embodiment is basically the same as that in Example 1, except that the complexation reaction is carried out at 80°C.
[0089] Comparative Example 1
[0090] The preparation method of the photocatalyst provided in this comparative example is basically the same as that of Example 1, except that glycerol is replaced by an equal molar amount of choline chloride, that is, glycerol is not added during the preparation process.
[0091] Comparative Example 2
[0092] The preparation method of the photocatalyst provided in this comparative example is basically the same as that of Example 1, except that choline chloride is replaced by an equal molar amount of glycerol, that is, choline chloride is not added during the preparation process.
[0093] Comparative Example 3
[0094] The preparation method of the photocatalyst provided in this comparative example is basically the same as that of Example 1, except that the mixed solution of choline chloride-glycerol-water is replaced with an equal volume of water, that is, choline chloride and glycerol are not added during the preparation process.
[0095] Comparative Example 4
[0096] The photocatalyst provided in this comparative example is ferric oxide.
[0097] Comparative Example 5
[0098] The photocatalyst provided in this comparative example is oxyferric chloride.
[0099] Comparative Example 6
[0100] The photocatalyst provided in this comparative example is zinc ferrite.
[0101] Experimental example
[0102] The tetracycline degradation test was carried out using the magnetic composite photocatalysts prepared in the above embodiments and the photocatalysts prepared in the comparative examples. After the tetracycline degradation test was completed, the photocatalysts were recovered, and the removal rate and recovery rate of tetracycline by each group of photocatalysts were calculated. The results are shown in Table 1.
[0103] The test method of the tetracycline degradation test is as follows: 100 ml of a 10 mg / L tetracycline solution is transferred to a reactor, the initial absorbance of the tetracycline solution is measured by a UV-visible spectrophotometer, a weighed photocatalyst (100 mg) is added to the tetracycline solution, illumination (40 W visible light) is started, the solution is stirred, and timing is started; a tetracycline solution (5 ml) is taken every 30 minutes, and after centrifugation and magnetic separation, the absorbance of the supernatant is measured by a UV-visible spectrophotometer to examine its change over time; when the absorbance of the supernatant does not change over time, it indicates that the reaction has reached equilibrium, the removal rate of the tetracycline solution by each photocatalyst is calculated, and the magnetic composite photocatalyst is separated by a magnet, and then washed alternately with anhydrous ethanol and distilled water, and then placed in an oven for drying, the obtained dried magnetic composite photocatalyst is repeatedly used in the photocatalytic degradation of tetracycline experiment, and the antibiotic removal rate of each photocatalytic experiment is calculated.
[0104] Table 1 Removal rate of tetracycline solution by each photocatalyst
[0105] Group Removal rate of tetracycline solution / % Example 1 90 Example 2 95 Example 3 99.5 Example 4 87 Example 5 85 Example 6 92 Example 7 93 Comparative Example 1 27.1 Comparative Example 2 52.1 Comparative Example 3 35 Comparative Example 4 25 Comparative Example 5 41 Comparative Example 6 30.8
[0106] It can be seen from Table 1 that the magnetic composite photocatalyst prepared in each embodiment has a high removal rate for tetracycline, and the removal rate is ≥85%, especially in Embodiment 3, which is as high as 99.5%.
[0107] The removal rate of the magnetic composite photocatalyst prepared in Example 1 for tetracycline solution changes with the treatment time as shown in FIG. Figure 2 The removal rate of the magnetic composite photocatalyst prepared in Example 2 for tetracycline solution changes with the treatment time as shown in Figure 3 The removal rate of the magnetic composite photocatalyst prepared in Example 3 for tetracycline solution changes with the treatment time as shown in Figure 4 The removal rate of the magnetic composite photocatalyst prepared in Example 4 for tetracycline solution changes with the treatment time as shown in Figure 5 The comparison of the removal rate of tetracycline by the first photocatalytic tetracycline solution experiment and repeated recycling three times by the magnetic composite photocatalyst prepared in Example 3 is shown in the figure below. Figure 6 shown.
[0108] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A method for preparing a magnetic composite photocatalyst for removing tetracycline, characterized in that: The steps include: The choline chloride, glycerol, water, zinc source, iron source and citric acid are mixed and subjected to complex reaction to obtain a sol; the pH of the sol is adjusted and then heated to obtain a gel; the gel is ignited to obtain a precursor; the precursor is calcined to obtain the magnetic composite photocatalyst for removing tetracycline; Wherein, the molar ratio of the zinc element in the zinc source to the iron element in the iron source is 1:1.4-2.4; The molar ratio of the choline chloride to the glycerol is 0.5-1.5:1.5-2.5; The ratio of the sum of the volumes of the choline chloride and the glycerol to the volume of the water is 10-25:2-20.
2. The method for preparing the magnetic composite photocatalyst for removing tetracycline according to claim 1, characterized in that: The ratio of the molar amount of the citric acid to the sum of the molar amounts of the zinc element in the zinc source and the iron element in the iron source is 0.75 to 1.25:
1.
3. The method for preparing the magnetic composite photocatalyst for removing tetracycline according to claim 1, characterized in that: The ratio of the sum of the volumes of the choline chloride, the glycerol and the water to the molar amount of the zinc element in the zinc source is 20-100 mL:1 mol.
4. The method for preparing the magnetic composite photocatalyst for removing tetracycline according to claim 1, characterized in that: The temperature of the complexation reaction is 40-95°C.
5. The method for preparing the magnetic composite photocatalyst for removing tetracycline according to claim 1, characterized in that: The pH of the sol is adjusted to a pH range of 7.5-9.
6. The method for preparing the magnetic composite photocatalyst for removing tetracycline according to claim 1, characterized in that: The calcination temperature is 500-1000°C.
7. The method for preparing the magnetic composite photocatalyst for removing tetracycline according to claim 1, characterized in that: The calcination holding time is ≥40min.
8. The method for preparing the magnetic composite photocatalyst for removing tetracycline according to claim 1, characterized in that: The calcination step further includes water washing and drying steps.
9. A magnetic composite photocatalyst for removing tetracycline, characterized in that: The invention is mainly prepared by the preparation method of the magnetic composite photocatalyst for removing tetracycline as claimed in any one of claims 1 to 8, wherein the magnetic composite photocatalyst for removing tetracycline comprises oxyferric chloride, zinc ferrite and ferric oxide.
10. Use of the magnetic composite photocatalyst for removing tetracycline as claimed in claim 9 in removing tetracycline.
Citation Information
Patent Citations
Efficient light fenton catalyst Ag3PO4 / CuO and preparation method thereof
CN105195185A
Method for processing organic wastewater through catalytic activation of peroxysulphate by means of visible light and FeOCl in synergetic mode
CN106517486A
Preparation method and applications of FeOCl / CNT composite film
CN109956529A
Composite photocatalyst for removing methylene blue as well as preparation method and application of composite photocatalyst
CN117772204A
Magnetic composite photocatalyst for removing dye as well as preparation method and application of magnetic composite photocatalyst
CN117797820A